Access to Capital in Rural Thailand: An Estimated Model of Formal vs. Informal Credit - Gine, Xavier (World Bank, Washington, DC, 2012)
The aim of this paper is to understand the mechanism underlying access to credit. The author focuses on two important aspects of rural credit markets in Thailand. First, moneylenders and other informal lenders coexist with formal lending institutions such as government or commercial banks, and more recently, micro-lending institutions. Second, potential borrowers presumably face sizable transaction costs obtaining external credit. The author develops and estimates a model based on limited enforcement and transaction costs that provides a unified view of those facts. The results show that the limited ability of banks to enforce contracts, more than transaction costs, is crucial in understanding the observed diversity of lenders.